Analisis Penerapan Standar K3 di Fasyankes (Klinik Kimia Farma Pasar Minggu Tahun 2021) - Devi Novriani; Ahmad Affan; Fajar Saputra (Lembaga Pengembangan Kinerja Dosen, 2024)
one of the factors that can influence job satisfaction. There is a lack of awareness in several clinics in Indonesia, especially at Kimia Farma Clinic in Pasar Minggu, South Jakarta, regarding K3 implementation standards and suboptimal health services. This research aims to find out how the implementation of K3 in clinics meets standards and to analyze problems related to the implementation of K3 at Kimia Farma clinic, Pasar Minggu. South Jakarta. The method used is a descriptive method by collecting retrospective and concurrent data. The research results obtained are that the Kimia Farma Pasar Minggu Clinic, South Jakarta is a health service place that already has an K3 commitment as evidenced by the availability of a Decree from the Owner of the Clinic Facilities regarding the implementation of K3 as well as a Decree from the K3 Implementation Team, the availability of competent human resources and supported by training and allocation of funds, available SOPs for Standard Precautions Compliance Levels, available B3 waste management carried out by third parties, available SOPs and PPE related to waste management, available SOPs for reporting work accidents, reporting work-related illnesses and available Emergency Response Teams or Red Code Teams.